Towards radiolabeled EGFR-specific peptides: alternatives to GE11 - Judmann, Benedikt; Wängler, Björn; Schirrmacher, Ralf; Fricker, Gert; Wängler, Carmen (Pharmaceuticals, 2023)
The human epidermal growth factor receptor (EGFR) is closely related to several cancer-promoting processes and overexpressed on a variety of tumor types, rendering it an important target structure for the imaging and therapy of several malignancies. To date, approaches to develop peptidic radioligands able to specifically address and visualize EGFR-positive tumors have been of limited success. Most of the attempts were based on the lead GE11, as this peptide was previously described to be a highly potent EGFR-specific agent. However, since it has recently been shown that GE11 exhibits an insufficient affinity to the EGFR in monomeric form to be suitable as a basis for the development of tracers based on it, in the present work we investigated which other peptides might be suitable as lead structures for the development of EGFR-specific peptidic radiotracers. For this purpose, we developed 68Ga-labeled radioligands based on the peptides D4, P1, P2, CPP, QRH, EGBP and Pep11, having been described before as EGFR-specific. In addition, we also tested three truncated versions of the endogenous EGFR ligand hEGF (human epidermal growth factor) with respect to their ability to specifically target the EGFR with high affinity. Therefore, chelator-modified labeling precursors of the mentioned peptides were synthesized, radiolabeled with 68Ga and the obtained radioligands were evaluated for their hydrophilicity/lipophilicity, stability against degradation by human serum peptidases, in vitro tumor cell uptake, and receptor affinity in competitive displacement experiments on EGFR-positive A431 cells. Although all NODA-GA-modified (NODA-GA: (1,4,7-triazacyclononane-4,7-diyl)diacetic acid-1-glutaric acid) labeling precursors could be obtained more or less efficient in yields between 5 and 74%, the 68Ga-radiolabeling proved to be unsuccessful for two of the three truncated versions of hEGF ([68Ga]Ga-8 and [68Ga]Ga-9), producing several side-products. For the other agents [68Ga]Ga-1-[68Ga]Ga-7, [68Ga]Ga-10 and [68Ga]Ga-11, high radiochemical yields and purities of ≥98% and molar activities of up to 114 GBq/µmol were obtained. In the assay investigating the radiopeptide susceptibilities against serum peptidase degradation, the EGBP-based agent demonstrated a limited stability with a half-life of only 66.4 ± 3.0 min, whereas the other tracers showed considerably higher stabilities of up to an 8000 min half-life. Finally, all radiotracer candidates were evaluated in terms of tumor cell internalization and receptor binding potential on EGFR-positive A431 cell. In these experiments, all developed agents failed to show an EGFR-specific tumor cell uptake or a relevant EGFR-affinity. By contrast, the positive controls tested under identical conditions, [125I]I-hEGF and hEGF demonstrated the expected high EGFR-specific tumor cell uptake (33.6% after 1 h, being reduced to 1.9% under blocking conditions) and affinity (IC50 value of 15.2 ± 3.3 nM). Thus, these results indicate that none of the previously described peptidic agents developed for EGFR targeting appears to be a reasonable choice as a lead structure for the development of radiopeptides for targeting of EGFR-positive tumors. Likewise, the tested truncated variants of the endogenous hEGF do not seem to be promising alternatives for this purpose.
Gesehen am 27.03.2023